2006
DOI: 10.2139/ssrn.928403
|View full text |Cite
|
Sign up to set email alerts
|

Has Globalisation Increased Inequality?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Previous empirical studies have shown that globalisation was positively correlated with income inequality over the period 1970–2000 especially in OECD countries (Dreher and Gaston, ; Gaston, ). The positive correlation was, however, not attributable to economic globalisation .…”
Section: Hypotheses and Empirical Evidencementioning
confidence: 96%
“…Previous empirical studies have shown that globalisation was positively correlated with income inequality over the period 1970–2000 especially in OECD countries (Dreher and Gaston, ; Gaston, ). The positive correlation was, however, not attributable to economic globalisation .…”
Section: Hypotheses and Empirical Evidencementioning
confidence: 96%
“…Traditionally, low-skilled workers are among the losers in industrial countries, whereas they are among the winners in developing or transition countries. Furthermore, globalization might also increases uncertainty, and, finally, might reversely impact individuals' relative income position (Dreher and Gaston, 2006), thus decreasing subjective wellbeing.…”
Section: Economic Factorsmentioning
confidence: 99%
“…Despite having better economic growth, poverty and the gap between the rich and poor still prevail (Easterly, 2001) not only in the less developed countries but also in the developed world (Gaston and Rajaguru, 2009). Although multiple factors are likely to impact income inequality, the globalization process continues to receive increasing attention (Gaston and Rajaguru, 2009;Dreher et al 2008). The proponents of globalization perceive the stage of economic development and international mobility of worker force (labor markets) as one of the most important channels influencing income inequality (Yabuuchi and Chaudhuri, 2007).…”
Section: Introductionmentioning
confidence: 99%